1996
DOI: 10.1016/s0896-6273(00)80255-x
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Defects Induced by Null Mutationof the isk Gene

Abstract: The isk gene is expressed in many tissues. Pharmacological evidence from the inner ear suggests that isk mediates potassium secretion into the endolymph. To examine the consequences of IsK null mutation on inner ear function, and to produce a system useful for examining the role(s) IsK plays elsewhere, we have produced a mouse strain that carries a disrupted isk locus. Knockout mice exhibit classic shaker/waltzer behavior. Hair cells degenerate, but those of different inner ear organs degenerate at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
257
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(269 citation statements)
references
References 65 publications
(22 reference statements)
6
257
0
6
Order By: Relevance
“…Mutations in both KCNQ1 and KCNE1 cause Jervell and Lange-Nielsen syndrome in humans (Neyroud et al 1997;Schulze-Bahr et al 1997), a syndrome associated with ventricular tachyarrhythmias of the heart and deafness. Knockout mouse models for both genes show a collapsed membranous labyrinth indicative of endolymph secretion failure and disruption of fluid homeostasis in the inner ear (Vetter et al 1996;Lee et al 2000;Casimiro et al 2001). A spontaneous mouse mutant, Punk Rocker, with a nonsense mutation in Kcne1 that results in a truncated protein, also shows an inner ear phenotype similar to the knockout mice .…”
Section: Genes That Affect Fluid Homeostasismentioning
confidence: 97%
“…Mutations in both KCNQ1 and KCNE1 cause Jervell and Lange-Nielsen syndrome in humans (Neyroud et al 1997;Schulze-Bahr et al 1997), a syndrome associated with ventricular tachyarrhythmias of the heart and deafness. Knockout mouse models for both genes show a collapsed membranous labyrinth indicative of endolymph secretion failure and disruption of fluid homeostasis in the inner ear (Vetter et al 1996;Lee et al 2000;Casimiro et al 2001). A spontaneous mouse mutant, Punk Rocker, with a nonsense mutation in Kcne1 that results in a truncated protein, also shows an inner ear phenotype similar to the knockout mice .…”
Section: Genes That Affect Fluid Homeostasismentioning
confidence: 97%
“…Further histological analysis of OHCs by electron microscopy excluded other changes at the cellular level such as apoptosis. Vacuoles are frequently seen as the first signs of (hair) cell death (Vetter et al, 1996). At 2 months of age, the numbers of outer hair cells containing vacuoles in heterozygous mice were especially high in the apical region of the cochleae, which is responsive to frequencies of approximately 4 kHz (Ou et al, 2000), whereas in the middle (responsive to 16 kHz) and basal regions (responsive to 32 kHz), these numbers remained low.…”
Section: Outer Hair Cells Are Affected By Both Histological and Physimentioning
confidence: 99%
“…In contrast, others, such as stargazer (Khan et al 2004), het (Paffenholz et al 2004), isk (Vetter et al 1996), tlt and mlh (Hurle et al 2003), Pmca2 (Kozel et al 1998), shaker/waltzer (Sun 2001), and hscy (Longo-Guess et al 2005), have not been reported as having significant bony abnormalities. It is not known, however, if some of these animals may have relatively subtle changes in the anatomy of the temporal bone that have gone unnoticed.…”
Section: Introductionmentioning
confidence: 98%